2021
DOI: 10.1096/fba.2021-00073
|View full text |Cite
|
Sign up to set email alerts
|

Critical cysteines in the functional interaction of adenylyl cyclase isoform 6 with Gαs

Abstract: Pulmonary vasodilation is mediated by endothelial nitric oxide acting via the cyclic guanosine monophosphate pathway, and by circulating prostacyclin acting through the cyclic adenosine monophosphate (cAMP) pathway. Persistent pulmonary hypertension of the newborn is a syndrome characterized by disruption of circulatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
(88 reference statements)
1
5
0
Order By: Relevance
“…It is known that small or local perturbations can produce significant RMSD changes. The magnitude of RMSD we report following a single residue substitution mutation is in line with what we have previously obtained from single-point mutation analyses [ 44 ]. Similar magnitude RMSD changes are described by others after the substitution of hydrophobic alanine for a neutral (e.g., threonine) or hydrophilic (e.g., asparagine) residue [ 54 ], and from single point mutations occurring spontaneously in the SARS-CoV2 protease that result in altered molecular dynamics [ 55 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is known that small or local perturbations can produce significant RMSD changes. The magnitude of RMSD we report following a single residue substitution mutation is in line with what we have previously obtained from single-point mutation analyses [ 44 ]. Similar magnitude RMSD changes are described by others after the substitution of hydrophobic alanine for a neutral (e.g., threonine) or hydrophilic (e.g., asparagine) residue [ 54 ], and from single point mutations occurring spontaneously in the SARS-CoV2 protease that result in altered molecular dynamics [ 55 ].…”
Section: Discussionsupporting
confidence: 90%
“…Despite the increase in expression, we observed that the activity of the AC6 isoform is significantly inhibited under hypoxia [ 17 ]. Hypoxia may impair AC6 interaction with its key upstream activator Gαs [ 44 ] due to nitrosylation of AC6 at its interface with Gαs [ 22 , 45 ]. Similarly, we found nitrosyl group donor CSNO treatment decreases AC activity only in the AC6 isoform.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gαi association with membrane receptors is known to increase when it is nitrosylated ( Chao et al, 2021 ). We also reported in PASMC a switch from Gαs-to Gαi-signalling in a nitrosylating environment ( Bhagirath et al, 2022 ). Receptor G protein coupling dynamics deserve further examination in presence of ROS/RNS in order to elucidate the mechanisms for NO augmentation of hypoxic Ca 2+ mobilization.…”
Section: Discussionmentioning
confidence: 87%